Systematic Transfemoral Transarterial Transcatheter Aortic Valve Replacement in Hostile Vascular Access. Issue 1 (2nd January 2019) - Staniloae, Cezar S.; Jilaihawi, Hasan; Amoroso, Nicholas S.; Ibrahim, Homam; Hisamoto, Kazuhiro; Sin, Danielle N.; Lee, Hanah; Du, Run; Zhao, Zhen-Gang; Neuburger, Peter J.; Williams, Mathew R.
ABSTRACT: Background: Traditionally, hostile peripheral access patients undergo TAVR via alternative access. We describe the "transfemoral-first" (TF-1) approach in patients with hostile peripheral access. Methods: Clinical and procedural data were obtained for all TAVR cases performed from August 2016 to July 2017. Computed tomography was used to assess iliofemoral arteries. Patients were divided into three femoral access groups: routine, hostile, and prohibitive. We attempted TF access in all patients with routine and hostile access. Hostile access was defined as: (1) arterial segments with diameter <5.0 mm; or (2) <5.5 mm with severe calcification (270–360° arc of calcification) or severe tortuosity; or (3) severe tortuosity along with severe calcification. Outcomes of the hostile access group patients who underwent TF-1 are described. The primary endpoint was successful completion of the procedure without major complications by the intended route. The secondary endpoints were procedural complications as defined by the VARC-2 criteria. Results: Of 377 consecutive patients, 99.5% underwent TF-1 TAVR; two patients (0.4%) had prohibitive access. Twenty-eight (7.4%) patients had hostile access with access side mean minimal lumen diameter of 4.7 mm (range 3.8–5.4 mm). Twenty-six (92.8%) were successfully treated with TF-1 strategy. Twelve (42.8%) of the 26 patients underwent preparatory endovascular treatment prior to TAVR during the same operating room visit. There was 1 (3.5%) major or life-threatening bleeding complication and 2 (7.1%) major vascular complications. There were no deaths or strokes. Conclusion: Using the safe and effective endovascular approach, TF-1 TAVR is feasible for all-comers—including those with hostile access—with low complication rate. Larger studies are warranted to validate this approach.